Ultrasonography Findings in the Proximal Sciatic Nerve and Deep Gluteal Muscles in 29 Dogs With Suspected Sciatic Neuritis - Toijala, Tiiu M.; Canapp, Debra A.; Canapp, Sherman O. (Frontiers in Veterinary Science, 2021)
The present study aimed to describe the ultrasonography technique and analyze the ultrasonographic findings of the proximal sciatic nerve and deep gluteal muscles in dogs with suspected sciatic neuritis. The records of 29 dogs that underwent musculoskeletal ultrasound of the sciatic nerve and deep gluteal muscles were retrospectively evaluated. Both right and left sides were evaluated. Abnormal findings were unilateral in 28/29 (97%) of the dogs. The muscles examined included the piriformis muscle, gemelli muscles, internal obturator muscle, and medial gluteal muscle. Data included signalment, purpose of the dog, orthopedic examination findings, lameness examination findings, other diagnostic imaging findings, and ultrasonography findings. Irregular margins of the sciatic nerve were recorded in 76% of the dogs. The diameter of the sciatic nerve on the affected limb was significantly larger than the nerve on the contralateral, unaffected side (p < 0.00001). The mean ± standard deviation (SD) of the sciatic nerve inner diameter between the unaffected and affected limbs was 15 ± 14.66%. The mean ± SD in sciatic nerve outer diameter was 12 ± 7.71%. Abnormal ultrasonographic findings in at least one of the examined muscles were found in 28/29 (97%) of the dogs and included changes in echogenicity in 28/29 (97%) of the dogs, loss of detail in muscle fiber pattern in 5/29 (17%) of the dogs, and impingement between the sciatic nerve and piriformis muscle in 6/29 (21%) of the dogs. The most common underlying diagnosis was lumbosacral stenosis in 9/29 (31%) of the dogs. The most common sport was agility for 21/29 (71%) of the dogs. Repetitive jumping may predispose to both lumbosacral disease, through dynamic compression, and changes within the piriformis muscle, due to overuse of the muscle leading to irritation to sciatic nerve. Ultrasonography is considered a safe and non-invasive diagnostic method to evaluate the sciatic nerve and deep gluteal muscles of dogs, and provides additional guidance for diagnostics and rehabilitation planning. This is the first study documenting ultrasonography findings in a case series of the sciatic nerve and deep gluteal muscles and their pathology in dogs.